Pengetahuan Keselamatan Kerja dan Kecelakaan Kerja pada Pekerja Proyek: Occupational Safety Knowledge and Work Accidents among Project Workers - Roni Iryadi; Mitha Erlisya Puspandhani; Sigit Winarto; Sonny Fitriawan Imbara; Elvi Yunianti (MPI Press, 2026)
Background: Occupational safety knowledge is an important individual factor in preventing unsafe actions among project workers. This study aimed to analyze the relationship between occupational safety knowledge and work accidents among project workers at PT Adiwarna Anugerah Abadi. Methods: This quantitative analytic observational study used a cross-sectional design. A total of 66 project workers were selected using simple random sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data were analyzed using univariate analysis and bivariate analysis. Fisher exact test was used because the contingency table contained a small expected frequency. Results: Most respondents had senior high school/vocational education (87.8%), work experience of more than five years (59.1%), and were aged 21-30 years (56.0%). The occupational safety knowledge and work accident instruments were valid and reliable, with Cronbach alpha values of 0.875 and 0.890. Workers with sufficient safety knowledge had a higher proportion of work accidents than workers with good knowledge (71.4% vs. 20.3%). Safety knowledge was significantly associated with work accidents (p=0.010; OR=9.79; 95% CI=1.69-56.79). Conclusion: Occupational safety knowledge was associated with work accidents among project workers. Periodic safety education, toolbox meetings, supervision, and reinforcement of safe work procedures are needed to maintain a safer work environment.